IMPLEMENTASI KEBIJAKAN PERCEPATAN PENURUNAN STUNTING DI KELURAHAN TANJUNG MAS - Fitriani, Neti; Yuniningsih, Tri; Djumiarti, Titik (Journal of Public Policy and Management Review, 2025)
Stunting is a significant issue in Indonesia, with the rate reaching 21.5% in 2023, only a 0.1% decrease from the previous year, and not meeting the WHO target of 20% or the RPJMN 2020- 2024 target of 17.8% in 2023. Tanjung Mas Village in Semarang City, as a priority area for accelerating the reduction of stunting, still recorded 89 cases of stunting, the highest in the city, while other villages have achieved zero stunting status. This study aims to analyze the implementation of the stunting reduction acceleration policy in this village, using a descriptive qualitative approach and data collection through interviews and documentation. The theory used is the policy implementation model by Van Meter and Horn. The results show that the implementation of the stunting reduction acceleration policy in Tanjung Mas Village has been quite effective. However, there are several obstacles, including the lack of training for the Head of Social Welfare in the village, a shortage of youth cadres, limited budget allocation in the village and Posyandu, and the economic and social conditions of the community.